Role of thermal and electric field effects during the pre-treatment of fruit and vegetable mash by pulsed electric fields (PEF) and ohmic heating (OH). (August 2018) - Mannozzi, C.; Fauster, T.; Haas, K.; Tylewicz, U.; Romani, S.; Dalla Rosa, M.; Jaeger, H.
Abstract: The aim of this work was to quantify the recovery of juice and bioactive compounds of apple and carrot mashes treated by the electrotechnologies (PEF or OH) at different pre-heating temperatures (40, 60 or 80 °C), considering thermal and electric field based cell disintegration. In general, a higher cell disintegration resulting from the applied pre-treatments also resulted in higher juice yield (around 10% increase for carrot and 5% for apple compared to untreated). Regarding the carotenoid content of obtained carrot juices, only the PEF pre-treatment at 20 °C resulted in an increased extractability. A release of total polyphenols from apples into the juice increased in all pre-treated samples compared to the control. This study suggests that a combined pre-treatment can further improve the cell disintegration and juice yield and may have the potential to increase the recovery of bioactive compounds depending on the treatment parameters. Industrial relevance: Thermal treatment followed by PEF or conducted by OH can still improve the cell disintegration and yield of juice. Moreover, the combination of thermal and electric field effects may also improve the recovery of bioactive compounds depending on the chosen treatment conditions. Therefore, the combined treatments show high potentiality for the application at industrial level to improve the release of the juice and at the same time to obtain novel products with high quality. Highlights: Thermal treatment followed by PEF or OH improved cell disintegration and juice yield. Polyphenol content increased due to the thermal effects. Stronger electropermeabilization effect for juice yield of PEF than OH treated samples.